BAKTERI DAN JAMUR DIBAWAH TEGAKAN MANGROVE DI DESA TOLAI BARAT KECAMATAN TORUE KABUPATEN PARIGI MOUTONG - Pattalolo, Ade Kurniawati H.; Toknok, Bau; Sudhartono, Arief (Jurnal Warta Rimba, 2020)
Soil microbes such as bacteria and fungi affect soil fertility. Microbes are important aspects that  role in weathering of organic matter and nutrient cycling. The study conducted from February to April 2019. Analysis bacteria and fungi carried the Soil Science Unit Laboratory of Faculty of Agriculture, Tadulako University. This study aims  determine the bacterial colonies and fungi found under mangrove stands in Tolai Barat Village, Torue sub-district, Parigi Moutong District. The study a field survey method to determine the location of soil sampling in each type of mangrove. soil samples were taken from  dominant mangrove such  Rhizophora mucronata, Rhizophora apiculata, Sonneratia alba, Bruguiera gymnorrhiza, and Bruguiera sexangula. Each type  repeated 3 times to get 15 sample. Then the soil sample is cut to the depth 0-15 and 15-30 so that 30 samples and compiled into 10 samples. The results showed that  fhighest number of fungi and bacterial colonies in the upper layer, namely 0-15 cm deep. The highest  fungal colonies were found in Rizophora apiculata (580 x 104 CFU gr-1), Sonnertia alba (330 x 104 CFU gr-1), Bruguiera gymnorrhiza (61 x 104 CFU gr-1), Bruguiera sexangula (35, 35 0 x 104 CFU gr-1) and Rizophora mucronata (20 x 104 CFU gr-1), while the highest number of colonies found in Rizophora apiculata (5200 x 105 CFU gr-1), Sonneratia Alba (3700 x 105 CFU gr-1), Rizophora mucronata (260 x 105 CFU gr-1), Bruguiera sexangula (63 x 105 CFU gr-1) and Bruguiera gymnorrhiza (50.0 x 105 CFU gr-1).Kata kunci: Mangrove, Bakterial, Fungi